Social capital and destination strategic planning. (December 2018) - Soulard, Joelle; Knollenberg, Whitney; Boley, B. Bynum; Perdue, Richard R.; McGehee, Nancy Gard
Abstract: Improving stakeholder engagement is a critical challenge for destination strategic planning. Using social capital as a theoretical lens, this paper explores the social dynamics which facilitate or inhibit successful tourism destination planning. Working with five recently completed destination plans (3 USA states, an Australian state, and an Oceanic country), in-depth interviews of 74 stakeholders explored the dimensions of trust, reciprocity, and cooperation in the contexts of bonding and bridging social capital. The study's results suggest stakeholder support for destination strategic plans will increase as bonding and bridging social capital intensifies. Recommendations are provided both for destination strategic planning processes as well as for how to best implement strategic plans. Further research examining the applications of social capital theory is recommended. Highlights: Using social capital as a theoretical lens, this paper explores the dynamics of successful tourism destination planning. In-depth interviews with 74 stakeholders explored trust, reciprocity and cooperation in bonding and bridging social capital. As social capital increases, stakeholder support for destination strategic plans also increased. Social capital was explored concerning stakeholder response to both strategic plan development and implementation.